Determining the Dose of Radiation and Radurisation Effects on the Antioxidant Activity of Fish and the Thermophysical Characteristics of Fish Muscle Tissue - Roza T. Timakova; Sergey L. Tikhonov; Nataliya V. Tikhonova; Sergey V. Shikhalev (Foods, 2019)
The aim of this article is to develop a method for determining the dose of radiation in the processing of chilled fish and its effect on the antioxidant activity and thermophysical characteristics of muscle tissue. Radiation processing of chilled fish was performed using a linear electron accelerator model LEA-10-10S2. The dose of radiation was determined by the method of electron-paramagnetic resonance. After being treated with ionizing radiation, the cooled fish meets the requirements of the technical regulations of TR TU 021/2011 “On food safety„ and TR EAEU 040/2016 “On the safety of fish and fish products„. As a result of our research, a correlation was established between the area of the Electron Paramagnetic Resonance (EPR) signal and the absorbed dose of the radiation dose. We proved a decrease in the antioxidant activity of muscle tissue of fish with an increase in radiation dose. It is established that radiation treatment of chilled fish affects the thermophysical properties of muscle tissue.